Detection and Extraction of Heparin from Camel Lungs - Almeman, Ahmad; Abdulmajed, Kasem; Eid, Eltayeb E. (Current Pharmaceutical Biotechnology, 2019)
Background: Heparin is an essential drug used as an anticoagulant. Access to raw material suitable for heparin extraction is critical for creating a viable business opportunity. In Saudi Arabia, large amounts of raw material with potential for heparin extraction are wasted. Objective: To extract heparin and low-molecular-weight heparin (LMWH) from the camel lung, and measure its potency and activity. Methods: Heparin preparation included three steps: extraction, electrophoretic identification, and activity measurement. Fresh lung tissue (100 g) was minced and homogenized in a blender. Crude heparin extracts were prepared using Charles’s or Volpi’s method with slight modifications. Heparin was purified by electrophoresis using high-purity agarose gels in barium acetate buffer. The heparin activity of purified samples was assayed spectrophotometrically using commercial heparin kits. Results: Charles’s and Volpi’s extraction methods were simple and easy to establish. The yield was 90 mg crude heparin per 100 g of camel lung tissue following Volpi’s extraction protocol, whereas Charles’s method did not yield any heparin. The separation of heparin and LMWH by gel electrophoresis resulted in sharp and clear product bands using material prepared according to Volpi’s method. The heparin preparation had an anti-factor Xa activity of 37 IU/mg, indicating weak potency. Conclusion: Preparation of active heparin from camel lung tissue is a technology applicable in manufacturing. Further method development is needed to increase heparin purity and potency.
Keywords: dromedary